(untitled) (Environment & Health, 2020)
Objective: We developed the hygienic approaches to the assessment of planning decisions of the cities with different city-forming systems in terms of environmental pollution and risk to the health of the population. Methods: We used a set of general scientific and special research methods: bibliosemantic (for the analysis of regulatory and legal literature in the sphere of town-planning), theoretical (evaluation of the retrospective data of the research on the hygiene of planning of the settlements), analytical (development of the method for hygienic evaluation for various purposes), sanitary-epidemiological examination of master plans of the cities and SPZ for the objects of different hazard class, epidemiological and medico-statistical ones. We applied a risk assessment methodology to evaluate the risk of exposure of chemical pollutants of ambient air of the cities to the population. Results: The cities were studied taking into account the nature of the main sectors of the economy which form their city-forming base, as well as the features of the planning structure of the cities, which made it possible to identify the residential areas that were heavily influenced by the industrial enterprises and beyond their influence. The obtained data make possible to develop measures for environmental adjustment and to resolve reasonably the issues of general plans for urban development of the cities, taking into account the specificity of the development of main industrial complexes, to make management decisions on the ground, their implementation to create safe conditions for human vital acitvity. The processes of restructurization of the major branches of heavy industry, the consolidation and re-profiling of large industrial complexes and enterprises, and the intensive development of relatively small production facilities have become essential. In connection with the scarcity of land resources in the largest cities and megalopolises, the issues of the siting of existing filling stations and the design of prospective residential buildings near them, as well as the siting of designed filling stations under conditions of existing residential development, amid the rapid motorization of modern society are becoming increasingly important and require legislative regulation of the standardization of the SPZ for modern filling stations, taking into account not only hygienic requirements, but also the requirements of fire safety.